Examining influencer compliance with advertising regulations in branded vaping content on Instagram - Silver, Nathan A.; Bertrand, Adrian; Kucherlapaty, Padmini; Schillo, Barbara A. (Frontiers in Public Health, 2023)
Background: Existing FDA guidelines for social media ads, FTC disclosures for financial relationships, and Instagram’s stated internal policy against promoting tobacco use should limit the prevalence of tobacco content. However, evidence indicates that youth and young adults are exposed to vape advertisements on social media sites. Significant challenges to identifying posts that are subject to such guidelines exist. This research uses replicable criteria to identify vaping ads by influencers on Instagram and documents the extent to which such posts follow existing regulations. Methodology: An initial sample of 360 Instagram posts from 58 accounts, each with 100,000 or more followers, was used to identify 262 vape-related posts. We conducted content analysis of the 262 posts to determine the extent to which posts from the most prominent vaping influencers on Instagram complied with existing guidelines. Results: On average, the 58 Instagram accounts had 265,851.9 followers (SD=383,349.8) and 4,158 posts (SD=7,302.1). Nearly all posts featured vaping products, n= 239 (91.2%). Only 1 post complied with FTC guidelines, and 31 (14.3%) posts provided links to purchase the advertised product. Only 50 posts (20.9%) had warning labels. Finally, three posts use cartoon imagery despite the FDA’s warning about use of youth appealing advertisement. Discussion: Findings indicate that compliance with established regulations is negligible. Instagram's claim in 2019 that they would no longer permit the promotion of vaping products is not enforced. Moreover, violations of minimal FDA and FTC guidelines for social media promotion remain unenforced among a highly visible population of vaping influencers.